CHEMICAL COMPOSITION OF LEGUMINOUS TREE FOLIAGE AND EFFECT OF POLYETHYLENE GLYCOL ON GAS PRODUCTION AND IN VITRO DIGESTION PARAMETERS - Jaime Olivares Perez; F. Avilés-Nova; B. Albarrán-Portillo; S. Rojas-Hernández; A. Córdoba-Izquierdo; A. Villa-Mancera; O.A. Castelan-Ortega (Tropical and Subtropical Agroecosystems, 2014)
The objective was to determine the chemical composition, digestibility and in vitro digestion parameters in ten legume tree foliage using the in vitro gas-production method with and without polyethylene glycol (PEG). The foliages with higher protein content (P<0.001) (167.1 to 180.3 g/kg DM) were A. cochliacantha, L. esculenta, E. cyclocarpum and A. farnesiana; from the total phenols (P<0.001) (365.9 to 680.6 g/kg DM) L. divaricata, H. brasiletto and C. coriaria and condensed tannins (P<0.001) (35.4 to 88.0 g/kg DM) E. cyclocarpum, A. farnesiana, P. dulce, P. acatlense and G. sepium. The in vitro dry matter digestibility was different (P<0.001) among the foliages. The in vitro gas production (IVGP), in vitro organic matter digestibility, metabolizable energy (ME), gas yield (GY24h), short chain fatty acids (SCFA) and microbial mass production (PMM), were different (P<0.0001) among the foliage as a result of the species. The use of PEG increased (P<0.0001) IVGP, ME, GY24h and SCFA in H brasiletto, C. coriaria, L. esculenta and A. cochliacantha, but affect (P<0.0001) the partition factor and the PMM. The nutritional composition and fermentation parameters in vitro between foliages differ by effect of tree and use of PEG. It is concluded that chemical composition in the foliages affect the digestibility and fermentation parameters and use of PEG increased fermentation parameters in the foliages high in secondary compounds.